2012
DOI: 10.1103/physrevd.86.083530
|View full text |Cite
|
Sign up to set email alerts
|

New local duals in eternal inflation

Abstract: Global-local duality is the equivalence of seemingly different regulators in eternal inflation. For example, the light-cone time cutoff (a global measure, which regulates time) makes the same predictions as the causal patch (a local measure that cuts off space). We show that global-local duality is far more general. It rests on a redundancy inherent in any global cutoff: at late times, an attractor regime is reached, characterized by the unlimited exponential

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…7 The evaluation of the measure may be further complicated in realistic models where the boundaries of MðÞ might be rugged and fractal-like. In future work [45] it will be shown that the new scale factor cutoff is equivalent to a local measure, where such issues do not arise. More generally, the evaluation of global measures is usually dramatically simplified by considering local duals, due to the elimination of the infinitely redundant exponential self-reproduction underlying the attractor regime.…”
Section: Rate Equationmentioning
confidence: 99%
“…7 The evaluation of the measure may be further complicated in realistic models where the boundaries of MðÞ might be rugged and fractal-like. In future work [45] it will be shown that the new scale factor cutoff is equivalent to a local measure, where such issues do not arise. More generally, the evaluation of global measures is usually dramatically simplified by considering local duals, due to the elimination of the infinitely redundant exponential self-reproduction underlying the attractor regime.…”
Section: Rate Equationmentioning
confidence: 99%
“…For instance, the scalefactor, light-cone time and CAH+ cutoffs are dual to the local "fat geodesic", causal patch, and Hubbletube cutoffs, respectively [5,11,18]. This duality holds for a very specific choice of initial conditions for the local measures, with probabilities given by the dominant eigenvector of the rate equation for eternal inflation.…”
Section: Dominant Eigenvector Initial Conditionsmentioning
confidence: 99%
“…Essentially the same rate equation holds for the light-cone time cutoff, which is dual to the causal patch [11].…”
Section: A Rate Equationmentioning
confidence: 99%
See 2 more Smart Citations